2011
DOI: 10.1161/circgenetics.110.958058
|View full text |Cite
|
Sign up to set email alerts
|

PITX2c Is Expressed in the Adult Left Atrium, and Reducing Pitx2c Expression Promotes Atrial Fibrillation Inducibility and Complex Changes in Gene Expression

Abstract: Background-Intergenic variations on chromosome 4q25, close to the PITX2 transcription factor gene, are associated with atrial fibrillation (AF). We therefore tested whether adult hearts express PITX2 and whether variation in expression affects cardiac function. Methods and Results-mRNA for PITX2 isoform c was expressed in left atria of human and mouse, with levels in right atrium and left and right ventricles being 100-fold lower. In mice heterozygous for Pitx2c (Pitx2c), left atrial Pitx2c expression was 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
279
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(309 citation statements)
references
References 42 publications
21
279
1
2
Order By: Relevance
“…They furthermore showed that isolated PITX2c þ / À mice hearts were susceptible to AF during programmed pacing, because of shortening of atrial action potential durations (APDs) and the effective refractory period (ERP). 26 In line with these results, human studies have recently revealed that PITX2c expression is significantly decreased in patients with sustained AF, thus providing a molecular link between PITX2 loss-of-function and AF. 27 Although a lot of studies indicate PITX2 as having a role in AF, evidence regarding the expression of PITX2 and its target genes in patients with AF is still missing.…”
Section: The 4q25 Locusmentioning
confidence: 58%
“…They furthermore showed that isolated PITX2c þ / À mice hearts were susceptible to AF during programmed pacing, because of shortening of atrial action potential durations (APDs) and the effective refractory period (ERP). 26 In line with these results, human studies have recently revealed that PITX2c expression is significantly decreased in patients with sustained AF, thus providing a molecular link between PITX2 loss-of-function and AF. 27 Although a lot of studies indicate PITX2 as having a role in AF, evidence regarding the expression of PITX2 and its target genes in patients with AF is still missing.…”
Section: The 4q25 Locusmentioning
confidence: 58%
“…5.1) [62,65,66]. Jako potencjalne mechanizmy leżące u podłoża zwiększonego ryzyka AF u nosicieli częstych wariantów genetycznych postuluje się zmiany charakterystyki potencjału czynnościowego komórek przedsionków [67][68][69][70], przebudowę przedsionków oraz zmodyfikowaną penetrację rzadkich defektów genetycznych [61]. Warianty genetyczne mogłyby w przyszłości stać się użyteczne podczas doboru pacjentów do strategii kontroli rytmu serca lub kontroli częstości rytmu komór [71][72][73][74].…”
Section: Skłonność Genetycznaunclassified
“…The gene most closely located to the risk variants encodes the two-domain transcription factor, PITX2. Low expression levels of PITX2 mRNA induce complex left atrial gene expression changes, without apparent structural alter ations, that predispose to AF 19,67 . Thus, altered expression of atrial ion channels as a result of genetic alterations in the atria could be a common path by which subtle genetic changes predispose patients to AF, subsequently influencing the response to antiarrhythmic drugs 68 .…”
Section: Ion-channel Dysfunctionmentioning
confidence: 99%
“…Unfortunately, most of these current approaches are disconnected from our understanding of the major mechanisms that cause AF 1,13,14 1,2,7,19,20 Abstract | Despite remarkable advances in antiarrhythmic drugs, ablation procedures, and stroke-prevention strategies, atrial fibrillation (AF) remains an important cause of death and disability in middle-aged and elderly individuals. Unstructured management of patients with AF sharply contrasts with our detailed, although incomplete, knowledge of the mechanisms that cause AF and its complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation